Review on Fresh Fruit Bunch (FFB) collector mechanization in Malaysia oil palm plantation field / Masro Masag - Masag, Masro (Faculty of Plantation and Agrotechnology, 2018)
Oil palm (Elaeis guineensis) was largest cultivated in Malaysia land included Borneo Sabah and Sarawak. The increased of cultivation oil palm area was introduced Malaysia as a second largest palm oil producer in the world. Increasing of land usage for cultivation oil palm was increased the worker demand and the production cost. The adopted of farm mechanization technology especially for collecting and evacuation FFB reduced the manpower dependency and increase the productivity of the worker. Mechanization was developed for evacuated oil palm FFB such as Mini Tractor Grabber (MTG), Mechanical Buffalo (Badang), Mobile Bunch Catcher (MBC), Three-wheeler evacuation machine and many more. Each mechanization was shown their performance and productivity in-field operation. The particular land condition in Malaysia also was considered for designing the machine to suit on topography and soil condition in-field. Based on journal published, the MTG was commonly used in oil palm plantation field. This is because based on the performance of MTG in-field operation and others function such as spraying herbicide, manuring, and transportation for workers.